The economic geography of labour migration: Competition, competitiveness and development - d'Artis Kancs (Economics and Econometrics Research Institute (EERI), 2006)
The present paper studies labour migration in the enlarged EU. Adopting the Krugman's framework of the New Economic Geography, we are able to study both the determinants of labour migration, such as market potential, wages, cost of living on one hand, and labour migration on the other hand simultaneously, which allows us to address important issues facing the traditional reduced form studies. Our empirical findings suggest that European integration would trigger labour migration between and within the Member States of the enlarged EU. Given that in our framework migrants are attracted by market potential, but they also affect market potential, the emergence of a core-periphery pattern through labour migration not very likely in the enlarged EU.
Keywords: F12; L11; R12; R23; 330; New economic geography; Market potential; Labour migration; Economic integration